Statistical techniques for high-voltage engineering - Hauschild, Wolfgang; Mosch, Wolfgang (Institution of Engineering and Technology, 1992)
This book sets out statistical methods that can be used in the preparation, execution, evaluation and interpretation of experiments of a random nature. It also includes the assessment of test methods used in high-voltage engineering from a statistical standpoint, and contains detailed sections on breakdown statistics of typical electrical insulating arrangements. Separate special areas of mathematical statistics such as statistical trial planning, questions of reliability, and stochastic processes are mentioned briefly. The extensive bibliography points the way to more advanced work. Emphasis is placed on easy comprehension, clarity, visual representation and practical relevance, and each process is explained using at least one example. The book is written from the engineer's point of view: mathematical deduction is dispensed with, while mathematical logic and terminological accuracy are ensured. This book is directed both at the practising engineer and at the student of electrical engineering at the stages of study involving independent creative experimental activity. Physicists and mathematicians encountering problems of application will also find the book invaluable.